β-Amyloid Plaque Reduction in the Hippocampus After Focused Ultrasound-Induced Blood–Brain Barrier Opening in Alzheimer’s Disease - D’Haese, Pierre-François; Ranjan, Manish; Song, Alexander; Haut, Marc W.; Carpenter, Jeffrey; Dieb, Gerard; Najib, Umer; Wang, Peng; Mehta, Rashi I.; Chazen, J. Levi; Hodder, Sally; Claassen, Daniel; et al. (Frontiers in Human Neuroscience, 2020)
The blood-brain barrier (BBB) limits therapeutic delivery in Alzheimer’s disease (AD) and other neurological disorders. Animal models have demonstrated safe BBB opening and reduction in β-amyloid plaque with focused ultrasound (FUS). We recently demonstrated the feasibility, safety, and reversibility of FUS induced BBB opening in the hippocampus and entorhinal cortex in 6 participants with early AD. We now report the effect of BBB opening with FUS treatment on β-amyloid plaque. Six participants underwent 18F-Florbetaben PET scan at baseline and one week after the completion of the third FUS treatment (60 days interval). PET analysis comparing the hippocampus and entorhinal cortex in the treated and untreated hemispheres revealed a decrease in the ratio of 18F-Florbetaben ligand binding. The standard uptake value ratios (SUVr) reduction ranged from 2.7-10% with an average of 5.05% (+/-2.76) suggesting a decrease in β-amyloid plaque.